Gayl Jones the language of voice and freedom in her writings - Clabough, Casey H. 1974- (McFarland & Co., 2008)
"Gayl Jones has a lived a life dedicated to the art of "verbal authenticity." This first single-author study of Gayl Jones recovers the work of an under-examined yet immensely skillful contemporary writer. The book addresses crucial themes germane to Jones's work, including questions of Afrocentrism, diasporas, mythopoesis, post-colonialism and globalization"--Provided by publisher.